Examining the causal relationship of entrepreneurial ecosystem and process: New contribution from an emerging economy - Dedi Kurniawan; Agus Sofian Eka Hidayat; Suwinto Johan (Jurnal Manajemen dan Pemasaran Jasa, 2021)
Existing literature on entrepreneurial ecosystems mostly ignores empirical research on the causal relationship between entrepreneurial ecosystems and their outputs. Therefore, this study examined the causal relationship of the entrepreneurial ecosystem on opportunity recognition, exploitation, and venture growth as its ecosystem outputs. This is quantitative research with the survey method. The study population is startup actors in Indonesia, consisting of owners, chief executive officers, and managers. The accidental sampling method with rigid screening questions was applied and questionnaires were distributed online through social media and messaging apps. The questionnaire was prepared using the Multi-dimensional Entrepreneurial Ecosystem Scale (MEES) to determine the ecosystem construct. Data were analyzed using the Structural Equation Modeling (SEM) techniques in the AMOS application. The result showed that the entrepreneurial ecosystem significantly affects opportunity recognition, exploitation, and venture growth. This fills the gap in this research and helps decision-makers in facilitating a better entrepreneurial ecosystem.